Sustaining gains in poverty reduction and human development in the Middle East and North Africa - Iqbal, Farrukh (Orientations in development., 2006)
This book reviews the experience of the MENA region with poverty and human development since the mid-1980s. It finds that poverty rates did not decline by much during this period while health and education indicators improved substantially. The stagnation of poverty rates is ascribed to the stagnation of the region?s economies during this period while the improvement in human indicators is likely due to several factors including improvement in the delivery of public health and education services.